Minimally Conjoined Omphalopagus Twins with a Body Stalk Anomaly - Hidehiko Maruyama; Takeshi Inagaki; Yusei Nakata; Akane Kanazawa; Yuka Iwasaki; Kiyoshi Sasaki; Ryuhei Nagai; Hiromi Kinoshita; Jun Iwata; Kiyoshi Kikkawa (Thieme Medical Publishers, Inc., 2015)
Abstract Introduction This report will discuss a case of minimally conjoined omphalopagus twins (MCOTs) with a body stalk anomaly (BSA). Case Report We experienced monochorionic diamniotic (MD) twins born at 31 weeks. One infant was suspicious of BSA before birth, and another infant was normal. But normal infant had anal atresia with small intestine which was inserted behind the umbilicus. Twins had very short common umbilicus and infant with BSA had intestinal conjunction, two appendixes at the site of the colon, and a blind-ending colon. We diagnosed MCOTs. Discussion On the basis of the Spencer hypothesis, the etiology of MCOTs was that MD twins shared a yolk sac. However, this could not explain the presence of a BSA. It is necessary to consider the possible reasons for a singleton BSA. In addition, intestinal fusion occurred unequally in this case, although two appendixes were found in the same place, which might have occurred because of the balanced fusion.